2021
DOI: 10.7759/cureus.17020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Accuracy of Modified CT Severity Index Score and Neutrophil-to-Lymphocyte Ratio in Assessing the Severity of Acute Pancreatitis

Abstract: Background Acute pancreatitis is an acute gastrointestinal emergency with significant morbidity and mortality if not treated. It can lead to local as well as systemic complications and has a prevalence of 51.07%. Laboratory investigations such as amylase and lipase and ultrasound scan are typically used for the diagnosis. A contrast-enhanced CT scan is considered the gold standard. Both laboratory and radiological investigation-based scoring systems have been reported in the literature and are in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…pancreatitis in the literature was estimated between 0.681 and 0.915, 8,[10][11][12][13][14] and a combined AUC of 0.82 was noted in a meta-analysis. 10 NLR48 was evaluated in a few studies and a meta-analysis for accuracy in predicting severe acute pancreatitis and AUCs between 0.739 and 0.93 were found.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…pancreatitis in the literature was estimated between 0.681 and 0.915, 8,[10][11][12][13][14] and a combined AUC of 0.82 was noted in a meta-analysis. 10 NLR48 was evaluated in a few studies and a meta-analysis for accuracy in predicting severe acute pancreatitis and AUCs between 0.739 and 0.93 were found.…”
mentioning
confidence: 90%
“…The neutrophil-lymphocyte ratio (NLR) has been suggested as a reliable marker for predicting inflammation progression and severity of pancreatitis in several studies. [7][8][9][10][11][12][13][14][15][16][17] Acute pancreatic inflammation activates inflammatory cytokines and proteolytic enzymes; 2 a high neutrophil number indicates an acute inflammatory response and a low lymphocyte number a deterioration in the general health condition combined with physiological stress. 10 The NLR can have physiological variations in healthy persons (0.78 to 3.53) and the baseline NLR can therefore influence increased values in acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTSI is a radiological scoring system based on CT scan results, designed to objectively quantify the severity of pancreatic inflammation, the presence of pancreatic necrosis, and extrapancreatic complications. Several studies have reported on the potential value of CTSI in predicting the severity and prognosis of AP [5][6][7]. However, the combined effect of CTSI with clinical parameters has not been sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%
“…At present, a variety of scores are used in the assessment of AP prognoses, such as Ranson, modified computed tomography severity index (MCTSI), and Bedside Index of Severity in Acute Pancreatitis (BISAP) scores (6)(7)(8). However, the calculation of those scores requires the use of numerous parameters and very complicated algorithms, which limits their use in clinical practice (8). Therefore, there is an urgent need for a simpler, faster, realtime tool to predict disease prognosis.…”
Section: Introductionmentioning
confidence: 99%